Produk Minuman Isotonik: Kajian Positioning Berdasarkan Uji Cochran - Husein Umar (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Isotonic beverages, known as energetic drinks, vitamins and serves to replace the ions of the body have long been sold in Indonesia with the various brands. This study seeks to determine whether isotonic drinks branded as Vitazone, Mizone and Pocari Sweat still fit the image initially or not. This study uses primary data from filling the questionnaire by 160 respondents. Data were analyzed using Cochran test. From the test results already known that isotonic drinks are not regarded as energetic drinks, vitamin and ion replaces the body again, but almost the same with drinks relieving thirst with delicious flavors that are easily found in stores at an affordable price.Keywords: Cochran Test, Positioning, Isotonic Beverages